Justified Belief and the Infinite Regress Argument - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 1981)
The background to this paper is the question of how rational belief is possible in the light of the commonly presented infinite regress in reasons. The paper investigates the neglected question of whether this regress is vicious. I argue that given the genuine requirements of rational belief, the regress would require the rational believer to hold an infinity of beliefs, which is impossible. The regress would not entail the rational believer holding an infinitely complex belief, which, admittedly, would be logically impossible.